Critérios diagnósticos e comparação do desempenho muscular e índices plasmáticos de mediadores inflamatórios em idosas sarcopênicas e não sarcopênicas - Patricia Parreira Baatista (2016)
Sarcopenia is a geriatric syndrome defined as an age-related decline in muscle mass (MM) and function. In 2010, the European Working Group on Sarcopenia in Older People (EWGSOP) recommended a definition and identification of sarcopenia syndrome. The Foundation for the National Institutes of Health (FNIH) Sarcopenia Project (2014) have also proposed clinically relevant cutoff points for muscle mass and strength loss. However, there is still not a universal consensus diagnosis criteria for this syndrome. Elevated plasma levels of interleukin-6 (IL-6) and soluble tumor necrosis factor-alpha (sTNFR1) are related to reduction in MM, strength and function. The behavior of these inflammatory markers, as well as objective functional performance parameters in sarcopenic and non-sarcopenic elderly are not well established. The general objective of the present study was to investigate diagnosis criteria and compare the behaviour of plasma levels of IL6 and sTNFR1 and muscular performance of sarcopenic and non sarcopenic community-dwelling elderly women. This project was approved by the Ethics Comitee of Universidade Federal de Minas Gerais. To be included subjects must be women, 65 years or older, "at risk of sarcopenia identified according to the EWGSOP, sedentary for at least three months, no race or social class distinction, residents in the community. Exclusion criteria were: cognitive impairment, self-reported neurological or reumathological diseases/sequalae, acute pain; dependent gait, câncer history on the previous 5 years, history of knee or hip arthroplasty and use of corticosteroids. In the first article, diagnostic accuracy of the index of muscle mass loss proposed by the FNIH (the sum of upper and lower limbs muscle mass adjusted by body mass, ASM/BMI) in relation to the values discriminated by the EWGSOP were checked. One hundred twenty two elder participated and gait speed (GS), handgrip strength (HGS) (Jamar® dynamometer) and MM (dual x-ray absorptiometry-DXA) were assessed. ASM/BMI index demonstrated insatisfatory results to identify loss of MM in elder women comparing to ASM/H2,(sum of upper and lower limbs muscle mass adjusted by height square), with value under the ROC curve of 0.516 (p=0.778), sensitivity of 41.5% and specificity of 61.7%. The second article compared measures of muscle performance and plasma levels of IL-6 and sTNFR1 between sarcopenic (SE) and non-sarcopenic (NSE) community-dwelling elder. Sixty-three subjects were included (32 NSE and 31 SE, according to the EWGSOP), assessed by HGS, concentric muscle performance of knee extensors at angular speeds of 600/s and 1800/s (isokinetic dynamometer), GS, MM (DXA) and plasma levels of IL-6 and sTNFR1. There were significant diferences between groups for mean power (p=0.014) and total work (p=0.0004) at angular speed of 1800/s and for plasma levels of sTNFR1 (p=0.013). SE showed worst muscle performance of knee extensors, specially at high velocities and NSE demonstrared lower plasma levels of sTNFR1 (p=0.013 - with lower values for SE). The NSE group showed higher significant values for BMI (p=0.001) and number of comorbidities (p=0.015) and these differences found between groups could have influenced the results related to inflammatory markers, since these factors have been linked to the chronic inflammatory condition in elderly.